Efectos del fortalecimiento del CORE en la alineación postural de adultos jóvenes que usan frecuentemente un dispositivo móvil - Carranza Carranza, Jéssica Paola (2018)
OBJECTIVE: Effect of the strengthening of CORE, scapular stabilizers and deep cervical flexors, contrasted to the strengthening of scapular stabilizing muscles and deep cervical flexors on postural alterations caused by the use of the mobile device. MATERIAL AND METHOD: We included 10 patients between 18 and 30 years, randomly divided into: a control group that performed strengthening of deep cervical flexor muscles and scapular stabilizers and an experimental group that performed strengthening of deep cervical flexors, scapular stabilizers and CORE. The initial and final evaluation composed of: postural analysis (Software Bio-GD), strength assessment by means of: CORE test, test for deep cervical flexors (Stabilizer Pressure Biofeedback) and on scapular stabilizers (Cobs dynamometer). Statistical analysis was performed with Student T-Test in paired samples for intragroups and unpaired samples for intergroups. RESULTS: Statistically significant results were shown in the control group in: a) distance from T3 to the medial border of the right scapula (p equal0,008), b) distance from T7 to the lower angle of the left scapula (p equal to 0.003883), c) Biering-Sorensen test (p equal 0.023410), d) test for deep cervical flexors (p equal to 0.008636), e) average force during horizontal abduction (left shoulder p equal to 0.005707), f) average of force during shoulder extension (right p equal to 0.009975), (left p equal to 0.011647). Intragroup experimental results were: a) distance from T3 to the medial border of the left scapula (p equal 0.027770), b) distance from T7 to the lower angle of the left scapula (p equal 0.003883), c) test 60 flexion (p equal to 0.038500), d) lateral plate test (right p equal to 0.002959), (left (p equal to 0.000715), e) test for deep cervical flexors (equal to 0.026254). The statistically significant intergroup results were: a) average force during horizontal abduction (right shoulder p equal to 0.025547), b) average strength during shoulder extension (right p equal to 0.035356), and (left p equal to 0.020848). Clinically significant results were obtained for all the variables. CONCLUSIONS: The joint strengthening of CORE, scapular stabilizers and deep cervical flexors has a greater effect on posture compared to the strengthening of scapular stabilizing muscles and cervical deep flexors only.